Developing and managing Bank Service Quality (BSQ) index / Firdaus Abdullah... [et al.] - Abdullah, Firdaus (Dr.); Suhaimi, Rosita (Assoc Prof); Saban, Gluma (Dr.); Hamali, Jamil (Assoc Prof) (UITM Sarawak,Kampus Samarahan, 2009)
As the financial landscape evolves dramatically and competition intensifies in the light of current global financial crisis, banking institutions need to respond to the radical change in market needs, and continually reassess their strategies and alternatives. Delivering quality service to customers is seen to be crucial for success and survival in today's competitive banking environment and it is an important route to competitive advantage and corporate profitability. Thus, it is essential to analyze the means of measuring and evaluating the service quality provided by banking institutions as they adjust to the dynamic changes in the environment, and to develop a new measuring tool that forms the basis for capturing the authentic determinants of service quality within the banking sector. However, previous studies have produced scales that bear a resemblance to the generic measures "of service quality, which may not be totally adequate to assess the perceived quality in the banking sector. Therefore, this study aims to design and validate a new measuring instrument of service quality, and ultimately to establish a national service quality index for the banking sector in Malaysia. The new Bank Service Quality Index (BSQ Index) is expected to be an important complement to traditional measures of economic performance, providing useful information to the banking institutions, shareholders, investors, government regulators, and customers. The proposed 29-item instrument has been empirically tested for unidimensionality, reliability and validity using both exploratory and confirmatory factor analysis. A factorial analysis suggests that service quality has three dimensions namely 'Systemization', 'Reliable Communication' and 'Responsiveness', and subsequent multiple regression analysis revealed that 'Systemization' is the most important service quality dimension within the banking sector.